Efektivitas Mirror Therapy terhadap Peningkatan Kekuatan Otot pada Pasien Stroke: Kajian Literatur - Tamba, Daud Halomoan; Iswoyo, Grace Vika; Koanak, Yohana Diana; Watania, Lani Natalia; Fangidae, Erniyati (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Stroke or Cerebrovascular disease is a disease caused by impaired brain function related to rupture or blockage of blood vessels that supply blood to the brain. Every year there are 13.7 million new cases of stroke and around 5.5 million deaths due to stroke. In Indonesia, it is estimated that around 2,129,326 people > 15 years have a stroke. Clinical manifestations that are often experienced by stroke patients are hemiparesis and hemiplegia so medical rehabilitation is needed. Mirror therapy is one of the non-pharmacological therapies that uses mirrors as a therapeutic medium. This literature review aims to describe the effectiveness of mirror therapy in increasing muscle strength in stroke patients. The method used was Thematic analysis: a simplified approach, with article searches using three databases namely Google Scholar, Medline, and JSTOR. Quality analysis of research methods has been carried out using PRISMA Flow Diagram and JBI Critical Appraisal Checklist.  The keywords used in the article search were "Effectiveness" AND "mirror therapy" AND "stroke patients" AND "Randomized Controlled Trial" and "Effectiveness" AND "mirror therapy" AND "stroke patients" AND "Randomized Controlled Trial". Four themes were obtained from the results of the analysis, namely, mirror therapy is effective for increasing muscle strength in stroke patients, the relationship between the characteristics of stroke patients and mirror therapy in increasing muscle strength, mirror therapy procedures in increasing muscle strength in stroke patients, the effectiveness of the combination of mirror therapy with conventional stroke rehabilitation therapy in increasing muscle strength. Mirror therapy as one of the non-pharmacological therapies that can be used in helping functional recovery of upper and lower extremity motor control in stroke patients. Keywords: Stroke, Muscle strength, and Mirror Therapy   ABSTRAK Stroke atau Cerebrovaskular disease merupakan penyakit yang disebabkan akibat gangguan fungsi otak yang berkaitan dengan pecah atau tersumbatnya pembuluh darah yang mensuplai darah ke otak. Setiap tahunnya tercatat 13,7 juta kasus baru stroke dan sekitar 5,5 juta kematian akibat penyakit stroke. Di Indonesia, diperkirakan sekitar 2.129.326 penduduk > 15 tahun mengidap stroke. Manifestasi klinis yang sering di alami oleh pasien stroke ialah hemiparesis dan hemiplegia sehingga diperlukan suatu rehabilitasi medis. Mirror therapy merupakan salah satu terapi non-farmakologi yang menggunakan cermin sebagai media terapi.Tujuan kajian literatur ini adalah menganalisa efektivitas mirror therapy dalam meningkatkan kekuatan otot pada pasien stroke. Metode yang digunakan adalah Thematic analisis: a simplified approach, dengan pencarian artikel menggunakan tiga database yaitu Google Scholar, Medline, dan JSTOR. Analisis kualitas metode penelitian telah dilakukan menggunakan Flow Diagram PRISMA dan JBI Critical Appraisal Checklist.  Kata kunci yang digunakan dalam pencarian artikel adalah “Effectiveness” AND “mirror therapy” AND “stroke patients” AND “Randomized Controlled Trial” dan “Efektivitas” AND “terapi cermin” AND “pasien stroke” AND “Randomized Controlled Trial. Empat tema didapatkan dari dari hasil analisa yaitu; Mirror therapy efektif untuk meningkatkan kekuatan otot pada pasien stroke, hubungan karakteristik pasien stroke dengan Mirror therapy dalam meningkatkan kekuatan otot, prosedur Mirror therapy dalam meningkatkan kekuatan otor pada pasien stroke, efektifitas kombinasi Mirror therapy dengan terapi rehabilitasi stroke konvensional dalam meningkatkan kekuatan otot. Mirror therapy sebagai salah satu terapi non- farmakologi yang dapat digunakan dalam membantu pemulihan fungsional kontrol motorik ekstremitas atas dan bawah pada pasien stroke. Kata kunci: Stroke, Kekuatan Otot dan Mirror Therapy